Expert Support Systems for New Product Development Decision Making: A Modeling Framework and Applications - Liberatore, Matthew J.; Stylianou, Anthony C. (Management Science, 1995)
A modeling framework that merges knowledge-based expert systems and decision support systems with management science methods for project evaluation is presented. In particular, the strategic decision to commit to full-scale development of a new product is considered. At the core of the framework are the methods and techniques used for acquiring, modeling and processing the expert knowledge and data. Methods and techniques used include scoring models, logic tables, the analytic hierarchy process, discriminant analysis, and rule-based systems. The suggested modeling approach obtains the benefits of normative modeling as well as the flexibility and developmental advantages of expert systems. Additional benefits include reduced information processing and gathering time, which can help to accelerate the product development cycle. Potential spin-offs of this research include applications for project evaluation throughout the product development cycle and other areas such as capital budgeting. Finally, a series of related case studies that have successfully implemented this framework is described.